Manajemen Pembelajaran Guru Matematika di MTS. Zia Salsabila - Khadijah Pasaribu; Rustam Rustam; Khairuddin Khairuddin (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
The aim of this research is to find out how mathematics teachers' learning management works. The research methodology uses qualitative research methods, the approach used in this research uses observation, interviews and documentation. The informant in this research was a mathematics teacher. This research data analysis uses data collection, data reduction, data presentation, and drawing conclusions. The data validity technique in this research uses source triangulation, method triangulation, theory triangulation. The research results show that mathematics teachers who implement good learning management, such as careful planning, use of appropriate learning media, and continuous evaluation, are able to increase student participation in the learning process. In addition, strategies such as problem-based learning, cooperative learning, and the use of educational technology have also proven effective in improving students' understanding of mathematical concepts and problem-solving skills.